4(4x + 3) + 6(2 - x) - 3(2x - 1) = 19

4(4x + 3) + 6(2 - x) - 3(2x - 1) = 19 16x + 12 + 12 - 6x - 6x + 3 = 19 4x + 27 = 19 4x = 19 - 27 4x = -8 x = -8/4 x = -2

Question

Asked 2/8/2009 9:40:33 AM

Updated 4/29/2016 2:19:41 PM

3 Answers/Comments

Edited by Andrew. [4/29/2016 2:19:39 PM]

s

Rating

8

4(4x + 3) + 6(2 - x) - 3(2x - 1) = 19

16x + 12 + 12 - 6x - 6x + 3 = 19

4x + 27 = 19

4x = 19 - 27

4x = -8

x = -8/4

x = -2

16x + 12 + 12 - 6x - 6x + 3 = 19

4x + 27 = 19

4x = 19 - 27

4x = -8

x = -8/4

x = -2

Added 4/29/2016 2:19:41 PM

This answer has been confirmed as correct and helpful.

35,955,889

questions answered

There are no comments.